Marine paleobiodiversity : responses to sea level cycles and perturbations - Ramkumar, Mu (Elsevier Ltd., 2016)
Marine Paleobiodiversity presents a concise history, development and current status of paleobiodiversity research, thus forming a reference work for beginners, graduates and postgraduates, who are interested in this subject and intend venture into serious research. This book provides a link-reference between text book and highly-specialized journal articles, and so will be valuable for a wide audience of geologists and climatologists.